PENGARUH PERLAKUAN SETEK RIMPANG TERHADAP PERTUMBUHAN DAN PRODUKTIVITAS GARUT (Maranta arundinacea L.) - ROSITA SMD; MONO RAHARDJO; SUDIARTO SUDIARTO (Pusat Penelitian dan Pengembangan Perkebunan, 2002)
Arrowroot (Maranta arundinacea L.) is usually propagated through young tillers or rhizome cuttings. A glass house and field tials were carried out at the Cimanggu Expeimental Insulation of the Research Institute for Spice and Medicinal Crops (RISMC), to assess 0k efect of rhizome patition and number of nodes of each parts on the viability of rhizomes, growth, productivity and starch content of arrowroot A clone of arrowroot (No. 17) collected from RISMC was used. One, two, three or four nodes of rhizomes cut at the base, middle or tip were used. A preliminary study was conducted in glass house from August to September 1999, where 40 samples of rhizomes were tested for their viability. Further study was conducted in the field from October 1999 to April 2000, to assess the growth, productivity and starch content of the rhizome from each treatment. The ield experiment was designed as a randomized block, arranged factorially in three replicates. The first factor was rhizome part (base, middle or tip) snd the second one was number of nodes (one, two, three or four nodes). Results showed that the highest percentage of plant growth, and seedling vigor of one month old were obtained from Uic four nodes tip rhizome cutting. At 6.5 month after planting the highest significant yield of resh rhizome was obtained from both base and middle parts rhizome cutting (324.04 and 326.46 g/hill), while the tip curling only produced 240.0 g/hill. The highest starch yield was obtained from the treatments of both the base and middle parts rhizome cutting i.e. 52.51 and 61.25 g/hill, while the tip cutting produced 47.19 g/hill. There was no interaction efect between the irst and the second factors on fresh rhizome yield. Highest signiicant fresh rhizome yield can also be obtained by using more than one node (320.96 - 337.69 g/hill), while a node cuting gave 198.65 g/hill only. Using base and middle rhizome cutting with 3 nodes gave the effective and eficient result, since it gave higher yield of the resh rhizome starch (70.38 and 72.41 g/hill).